ANALISIS KINERJA PSSI TERHADAP KEPUASAN SUPORTER TIM NASIONAL INDONESIA PERIODE 2024 - Lutfi Nugroho, Vemas; Alyanabilla, Deana; Nur Fauzan, Farhan; Nikita Putri, Larasati; Aditya, Toddy (Gapenas Publisher, 2025)
In the world of football, supporters play a crucial role and are often referred to as the